Inflation Dynamics and Labor Market Dynamics Revisited - Tommy Sveen; Lutz Weinke (Kiel Institute for the World Economy (IfW), 2007)
Firms adjust labor both at the intensive and at the extensive margin (see, e.g., Hansen and Sargent 1988). Moreover, employment adjustment is not frictionless (see, e.g., Mortensen and Pissarides 1994). What does this imply for inflation dynamics? To address this question we develop a New Keynesian model featuring two margins of labor adjustment as well as a simultaneous price-setting and employment decision at the firm level. We find that the presence of an empirically plausible labor adjustment decision at the firm level rationalizes strategic complementarities in price-setting which help explain inflation dynamics.
Keywords: 330